PENGUATAN KOMPETENSI PEDAGOGIK DAN PROFESIONAL GURU BIOLOGI DI ERA REVOLUSI INDUSTRI 4.0 (LP3M Universitas PGRI Mahadewa Indonesia, 2021)
Biology teachers are required to have high competence to make students able to face the challenges of the Industrial Revolution 4.0. The result of the teacher competence test for pedagogical and professional competence is an average of 45.82. This result is still below the national minimum competency standard. Thus, a broad and in-depth study is needed to improve teacher’s pedagogical and professional competence. Several research results indicate that to improve pedagogical and professional competence in biology learning, experimental learning strategies can be used. Experiments can (1) provide opportunities for teachers and students to develop logical thinking skills and abilities; (2) teachers and students are active in solving problems, thinking critically in analyzing existing problems and facts; (3) find concepts and principles, so that more meaningful learning activities are created with a conducive learning atmosphere.